THE DYNAMICS OF THE EDUCATIONAL MODEL OF PESANTREN IN THE NATIONAL EDUCATION SYSTEM - Hasyim, Yusuf (Pascasarjana Universitas Wahid hasyim Semarang, 2023)
Historically, pesantren education has undergone several changes, both related to the model, curriculum, objectives, and management system. The renewal was carried out so that pesantren education as an Indonesian Islamic educational institution was able to answer the challenges and demands of changing times. This paper aims to describe the Islamic education model of pesantren and its dynamics in the national education system, because until now pesantren still seems to be in two dilemma choices: whether pesantren will continue to maintain its tradition by maintaining its unique values or follow the times with all its dynamics. library research method with a descriptive analysis approach, the authors found that there are several models of Islamic boarding schools that are legally recognized in Law no. 18 of 2019 concerning Islamic Boarding Schools. that is; a. Islamic boarding schools that organize education in the form of the study of the Yellow Book; b. Islamic Boarding Schools that provide education in the form of Islamic Dirasah with Muallimin Education Patterns; or c. Islamic boarding schools that provide education in other forms that are integrated with general education. Keywords: model, pesantren education, national education